Publisher’s Note: Journal of Electronics and Electrical Engineering—A New Open Access Journal - Li, Russell (Journal of Electronics and Electrical Engineering, 2022)
Electrical engineering is a field of engineering that focuses on electricity and electronics, from microscopic computer components to large-scale electrical networks. It has been a key aspect of human advancement for centuries. Universal Wiser Publisher is pleased to announce the launch of a new journal—Journal of Electronics and Electrical Engineering.